Effects of food-related health concerns and risk perception on the consumption frequency of fresh vegetables - Adasme-Berríos, Cristian; Sánchez, Mercedes; Mora, Marcos; Díaz, José; Schnettler, Berta; Lobos, Germán (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
Consuming fresh vegetables certainly brings health benefits; however, these types of products may also contain biological, chemical and technological elements that can affect people´s health due to lack of food safety. We developed a conceptual model to explain the main relationships between food-related health concerns (FHCs) and risk perceptions (RPs) on consumption frequency of fresh vegetables (CFFV) from a food safety point of view. We applied a structured questionnaire to 1028 consumers in the Central and South Central zones of Chile, where the main agricultural production of the country is concentrated. Through a structural equation model, we determined the moderator effect of RP on the relationship between FHC and CFFV. As a result, CFFV is less if RP is present in the minds of the consumer, impacting the direct effect of FHC on CFFV. Finally, our results suggest that reducing risks associated with the production and commercialization of fresh vegetables can improve health concerns related to food and the consumption of fresh vegetables. Therefore, the state must improve surveillance systems of fresh vegetables commercialized in local markets.